The BRCA1 c.5434C→G (p.Pro1812Ala) variant induces a deleterious exon 23 skipping by affecting exonic splicing regulatory elements. Issue 6 (3rd June 2010) - Gaildrat, Pascaline; Krieger, Sophie; Théry, Jean-Christophe; Killian, Audrey; Rousselin, Antoine; Berthet, Pascaline; Frébourg, Thierry; Hardouin, Agnès; Martins, Alexandra; Tosi, Mario
Abstract : Background: A large fraction of the sequence variants of unknown significance or unclassified variants (UVs) could be pathogenic by affecting mRNA splicing. The breast and ovarian cancer susceptibility gene BRCA1 exhibits a large spectrum of sequence variation but only two variants, both located in exon 18, have been shown experimentally to affect splicing regulatory elements. The present study investigated the impact on splicing of the variant BRCA1 c.5434C→G (p.Pro1812Ala), identified in an ovarian cancer patient. This variant has previously been studied at the protein level with inconclusive results concerning its pathogenic role. Methods: Analysis of RNA from patient peripheral blood was performed by RT-PCR. The effect of the variant was tested by using splicing reporter hybrid minigene assays. Results: Using patient RNA analyses and hybrid minigene assays, we showed that this variant induces a major splicing defect, with skipping of exon 23, resulting in frameshift and predicted protein termination within the second BRCT domain. Moreover, we showed that the segment c.5420–5449 of BRCA1, in the centre of exon 23, exhibits splicing enhancer properties. This enhancement is abolished by the c.5434C→G mutation, indicating that the nucleotide change, in this highly conserved region, affects a splicing regulatory element. Bioinformatics analyses predict that the mutation c.5434C→G creates an hnRNPA1 dependent splicing silencer. Conclusion: These data, together with segregation data, argue for the classification of BRCA1 c.5434C→G as a pathogenic splicing mutation. These results also suggest that UVs in highly conserved nucleotide sequences of short exons may be good candidates for detecting functionally relevant splicing regulatory elements.